The impact of IFRS 17 transition mechanisms legislated by tax authorities on the GloBE effective tax rate of South Africa headquartered insurers - Modise, Keletso (Department of Finance and Tax, 2025)
During 2021 the Organization for Economic and Cooperative Development (‘OECD') released the Global Anti-Base Erosion Rules (‘GloBE Rules') as part of a two-pillar solution to address the challenges identified regarding the digitization of the economy. This significant development was preceded by the release of IFRS 17 Insurance Contracts in the same year and is issued by the International Accounting Standards Board. IFRS 17 is the culmination of a multi-year two phase project aimed at developing what is considered the first truly international insurance contract standard. The combination of the implementation of these two key developments and the practical impact of them on long-term insurers has not yet been fully ascertained. The research conducted seeks to determine the extent to which the transition mechanism legislated by tax authorities in response to and in preparation for the transition to IFRS 17 may impact the effective tax rate computed under the GloBE Rules. In addressing the research problem a two-pronged approach was taken, the first being a comparative analysis between the transition mechanisms opted for by tax authorities in South Africa and the United Kingdom, and the second being a case study using Discovery Limited, a South Africa headquartered MNE Group as the subject to illustrate the potential impact of the former, on the effective tax rate in the jurisdictions it operates in. The research indicated that the tax transition approach may have a significant impact on the effective tax rate of long-term insurers headquartered in South Africa resulting in the liability for top-up taxes.